Sebaran Alumni Program Studi Hukum Pidana Islam Dalam Dunia Kerja - Syahrul Anwar; Deden Najmudin; Muhammad Fadhlan Aziz (Jurnal Sosial Humaniora Sigli, 2025)
Graduates of the Islamic Criminal Law (HPI) Study Program at UIN Sunan Gunung Djati Bandung face challenges related to the suitability of their academic competencies with the demands of the world of work. This study aims to assess the distribution of alumni, the relevance of the curriculum, and the relationship between academic experience and career achievements. The methods used are purposive sampling with an online questionnaire and a sequential explanatory mixed method approach. The results show that the majority of HPI graduates have careers in education, public administration, and da'wah, while their involvement in the formal legal sector is limited; academic abilities support professionalism, but professional networks need to be strengthened. The novelty of this study lies in the integration of alumni distribution analysis with curriculum relevance evaluation, providing practical contributions to the development of learning strategies, internships, and alumni networks so that graduates are more adaptive and ready to face professional demands. Keywords : competence, islamic criminal law study program, opportunities